The effects of acute dopamine reuptake inhibition on performance - Roelands, B.; Hasegawa, H.; Watson, P.; Piacentini, M. F.; Buyse, L.; de Schutter, G.; Meeusen, R. (Medicine & Science in Sports & Exercise, 2008)
Introduction: Acute bupropion (dopamine/noradrenaline reuptake inhibitor) administration significantly improved time trial performance and increased core temperature in the heat (30° C).